PENGARUH KOLABOSARI PENCIPTAAN NILAI DAN ORIENTASI KEWIRAUSAHAAN TERHADAP INOVASI PRODUK - Munawar, Muhammad Meki; Suarsa, Senny Handayani (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
A culinary business in West Java is totally famous, especially for some cites: Bandung, Bogor, Purwakarta, Cirebon, Sumedang, Sukabumi and others. This culinary can attract not only local consumers but also domestic tourists to come and consume products that owners offer. To make the business sustain, the owners have to innovate their products. This research is present to examine and analyze the impact of co-creation value (CCV) and entrepreneurship orientation (EO) on product innovation. The samples of this study are the sixty owners of the culinary business in West Java, taken by the purposive sampling method. Furthermore, the data are collected by the survey method and analyzed by the variance-based structural equation model. After investigating and discussing the two proposed hypotheses, this research sum ups that co-creation value (CCV) and entrepreneurship orientation (EO) possess a positive impact on product innovation.